Lead-vanadate sorbents for iodine trapping and their conversion into an iodoapatite-based conditioning matrix - Pénélope, R.; Campayo, L.; Fournier, M.; Le Gallet, S.; Gossard, A.; Grandjean, A. (Frontiers in Chemistry, 2022)
New lead-vanadate based sorbents were synthesized with the aim to entrap and confine gaseous iodine in off-gas streams coming from reprocessing facilities of spent nuclear fuel. Their synthesis relies on the shaping of a lead-vanadate, lead sulfide and alginic acid mix as millimetric beads. These beads were calcined between 220°C and 500°C to remove organic alginic compounds template. However, according to the calcination temperature, lead sulfide could be partially oxidized, limiting iodine loading capacity. A compromise temperature between 290°C and 350°C was found to remove most of the alginic acid template and avoiding lead sulfide oxidation. These sorbents were tested for iodine trapping in static conditions at 60°C. They performed well with a sorption capacity up to 155 mg.g−1 by forming PbI2. Furthermore, these iodine-loaded sorbents could be easily converted into an iodine-containing lead-vanadate apatite matrix by spark plasma sintering. A dense sample was produced for a sintering temperature of 500°C under 70 MPa. Such a material could be suitable for radioactive iodine conditioning in deep geological disposal. Finally, lead-vanadate sorbents could provide an easy way to entrap and confine radioactive iodine from off-gas streams into a durable material within a few steps.